2008
DOI: 10.5694/j.1326-5377.2008.tb01627.x
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics: sorting the evidence from the myths

Abstract: Probiotics consist of yeast or bacteria, especially lactic acid bacteria. They are available as capsules, powder, fermented milks or yoghurts. Probiotics exhibit strain‐specific differences in their resistance to acid and bile, ability to colonise the gastrointestinal tract, clinical efficacy, and benefits to the health of the host. There is level I evidence for the use of probiotics in treating acute infectious diarrhoea and preventing antibiotic‐associated diarrhoea, with Lactobacillus rhamnosus GG and Sacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 58 publications
1
30
0
1
Order By: Relevance
“…Children receiving the multiple species product tended to have less time with diarrhoea and no patients vomited after the treatment was started. In previous studies that administered multiple species products similar to the one we used, other authors found a rather more pronounced effect, 30 hours [14,19] and 30-36 hours reduction in diarrhoeal duration [20-23], in comparison with the 26 hours reduction we found. Infants hospitalized in our study were admitted with severe diarrhoea and had intense clinical manifestations in comparison to outpatients with rotavirus diarrhoea; this could explain the less intense results obtained.…”
Section: Discussionsupporting
confidence: 49%
“…Children receiving the multiple species product tended to have less time with diarrhoea and no patients vomited after the treatment was started. In previous studies that administered multiple species products similar to the one we used, other authors found a rather more pronounced effect, 30 hours [14,19] and 30-36 hours reduction in diarrhoeal duration [20-23], in comparison with the 26 hours reduction we found. Infants hospitalized in our study were admitted with severe diarrhoea and had intense clinical manifestations in comparison to outpatients with rotavirus diarrhoea; this could explain the less intense results obtained.…”
Section: Discussionsupporting
confidence: 49%
“…This can be achieved by improving methods of animal husbandry, the eradication of diseases in animals, the optimal use of existing vaccines and the development of new vaccines [18, 19]. Generally, these interventions are aimed at reducing the development and incidence of resistant bacterial infections, thereby prolonging or restoring the effectiveness of existing antibiotics [20]. Importantly, a good programme for prevention of antibiotic resistance also includes an active system of surveillance for resistance, an active and effective infection control programme to minimize secondary spread of resistance, and the sensible use of antimicrobials in animal production systems [21].…”
Section: Discussionmentioning
confidence: 99%
“…Since modulation of the composition of intestinal microbiota by probiotics was demonstrated to be possible, probiotic intervention has the potential to counterbalance intestinal dysbiosis and thus restore health. The effectiveness of probiotic intervention has been studied in a number of human diseases, including IBD (CD, UC and pouchitis), IBS, constipation, diarrhoea (including AAD), colon cancer, cardiovascular disease, NEC, allergic diseases, obesity and metabolic disorders and these have been the subject of systematic reviews as well as Cochrane reviews (Gareau et al 2010; Iannitti and Palmieri 2010; Pham et al 2008; Sanz et al 2010; Weichselbaum 2010). With the possible exception of NEC and pouchitis, variable clinical effects are found.…”
Section: Modulation Of the Intestinal Microbiotamentioning
confidence: 99%